2011
DOI: 10.1016/j.jss.2010.11.092
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gender And Species Specific Formation of Aneurysms Using A Novel Method Of Inducing Abdominal Aortic Aneurysms

Abstract: Background-The objective of this study was to test a novel model of inducing AAA in different mouse strains and genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Another study concluded that genetic susceptibility is important in AAA development, as significantly more macrophages were found in C57BL/6 male than female mice, but there was no difference between sexes in B6129 mice. 60 Moreover, similar to human AAA tissue, male mice had higher levels of p308 which was correlated with increased AAA formation compared with female mice. 39 Finally, Johnston et al 38 showed that the protective effects in female mice were completely eliminated with deletion of aromatase.…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 88%
See 1 more Smart Citation
“…Another study concluded that genetic susceptibility is important in AAA development, as significantly more macrophages were found in C57BL/6 male than female mice, but there was no difference between sexes in B6129 mice. 60 Moreover, similar to human AAA tissue, male mice had higher levels of p308 which was correlated with increased AAA formation compared with female mice. 39 Finally, Johnston et al 38 showed that the protective effects in female mice were completely eliminated with deletion of aromatase.…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 88%
“…More recently, sex differences in AAA have been studied in different animal models, which include the intraluminal infusion of elastase in rats 57 or mice, 58 angiotensin II (AngII) infusion in mice deficient in apolipoprotein E (Apoe À/À ), 59 and direct application of elastase at the anterior wall of the abdominal aorta in mice (Table III). 60 In 2001, Lee et al 61 described an increased incidence of AAA in female mice deficient in the inducible form of nitric oxide synthase (Nos2 À/À ) compared with male mice (80% vs. 40%), suggesting that the interaction between estrogen and cellular NOS could influence nitric oxide production and that the absence of NOS2 might have enhanced local MMP9 activity and promoted aneurysmal degeneration in a sex-specific manner. Another study reported a higher incidence and a larger size of AAA in male than in female mice in Apoe…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 99%
“…In experimental animal models of aneurysms such as the elastase-induced model (Laser, Lu et al 2012) and Angiotensin II-induced model (Daugherty and Cassis 2004) some development of ILT has been observed.…”
Section: Properties Of the Iltmentioning
confidence: 99%
“…Despite this, each model offers mechanistic and therapeutic insight into key pathological components associated with AAA development and progression. Given the importance of the adventitial layer and its vasa vasorum in mediating inflammatory cell infiltration 49,59,60 , we selected a topical elastase-based approach to experimentally induce aortic inflammation and subsequent expansion 61 . The resulting inflammatory cell infiltration from the vasa vasorum has been shown to mimic observations in human aneurysms 6265 .…”
Section: Discussionmentioning
confidence: 99%